Nivolumab in never-smokers with advanced squamous non-small cell lung cancer: Results from the Italian cohort of an expanded access program. Issue 11 (November 2018) - Garassino, Marina Chiara; Crinò, Lucio; Catino, Annamaria; Ardizzoni, Andrea; Cortesi, Enrico; Cappuzzo, Federico; Bordi, Paola; Calabrò, Luana; Barbieri, Fausto; Santo, Antonio; Altavilla, Giuseppe; Ambrosio, Francesca; et al.
Objectives: Never-smokers may be a distinct subgroup among patients with advanced non-small cell lung cancer, appearing to benefit less from immunotherapy than smokers. We report results from never-smokers enrolled in the Italian cohort of the nivolumab expanded access program in pre-treated patients with advanced squamous non-small cell lung cancer. Materials and methods: Nivolumab (3 mg/kg every 2 weeks for ≤24 months) was available on physician request. Efficacy data included objective tumor response, date of progression, and survival information. Safety was monitored. Results: Overall, 371 patients received at least one dose of nivolumab, including 31 never-smokers (8%). Objective response rate, disease-control rate, and median overall survival were 23%, 45%, and 12.1 months (95% confidence interval: 3.7–20.4), respectively, in never-smokers, and 18%, 47%, and 7.9 months (95% confidence interval: 6.2–9.6), respectively, in the overall expanded access program population. Any-grade and grade 3–4 treatment-related adverse events were reported in 12 (39%) and 3 (10%) never-smokers, respectively, and in 109 (29%) and 21 (6%) patients, respectively, in the overall expanded access program population. Grade 3–4 treatment-related adverse events in non-smokers were increased transaminases (n = 2; 6%) and diarrhea (n = 1; 3%). Treatment-related adverse events led to treatment discontinuation in 4 non-smokers (17%) and in 26 patients (9%) overall. Conclusion: Pre-treated never-smokers with advanced squamous non-small cell lung cancer in this Italian expanded access program demonstrated efficacy and safety that were consistent with those in the overall expanded access program population and clinical trials. These results suggest that a proportion of never-smoker patients with squamous non-small cell lung cancer may be responsive to immunotherapy. Other factors, such as the tumor mutational load and the status of programmed death-ligand 1, anaplastic lymphoma kinase, and epidermal growth factor receptor, might play a potential key role.